2013
DOI: 10.1371/journal.pone.0055761
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Landscape of Aberrant DNA Methylation in Hepatocellular Carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the most common cancers and frequently presents with an advanced disease at diagnosis. There is only limited knowledge of genome-scale methylation changes in HCC.Methods and FindingsWe performed genome-wide methylation profiling in a total of 47 samples including 27 HCC and 20 adjacent normal liver tissues using the Illumina HumanMethylation450 BeadChip. We focused on differential methylation patterns in the promoter CpG islands as well as in various less stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 29 publications
8
87
1
Order By: Relevance
“…In contrast, the majority of hypomethylated CpGs in HCC were located away from CpG islands. Another group also reported that hypermethylated CpGs were mainly distributed close to transcription start sites, and the majority of hypomethylated CpGs were observed within 3′ regions of genes and intragenic regions [18]. …”
Section: Methylation Profile In Hccmentioning
confidence: 99%
“…In contrast, the majority of hypomethylated CpGs in HCC were located away from CpG islands. Another group also reported that hypermethylated CpGs were mainly distributed close to transcription start sites, and the majority of hypomethylated CpGs were observed within 3′ regions of genes and intragenic regions [18]. …”
Section: Methylation Profile In Hccmentioning
confidence: 99%
“…Absent or diminished expression of the GSTP1 gene in prostate cancer has been reported and is commonly due to CpG island GSTP1 promoter region methylation in the majority of prostate tumors (O90%), a phenomenon that is rarely detected in normal prostate or benign prostatic hyperplasia tissues. This gene has also been described as hypermethylated in breast carcinoma, an early event, which suggests its utility as a biomarker (Mahapatra et al 2012, Saxena et al 2012, Fukushige & Horii 2013, Song et al 2013. The DNA alkyl-repair gene MGMT, which removes mutagenic and cytotoxic alkyl adducts from genomic DNA, has also been found hypermethylated in this type of tumor (Kang et al 2004; Table 1).…”
Section: Ovarian Cancer Stromal Tumors (Frequency !3%)mentioning
confidence: 96%
“…A study of hepatitis B virus (HBV)-induced HCC compared DNA methylation profiles between tumor and adjacent tissue, this identified 1,640 hypomethylated and 684 hypermethylated CpG in the tumor. 14 Using a similar approach, Song et al 15 reported that 62,692 loci displayed differential methylation between HCC and surrounding tissue, of which a remarkable 61,058 were hypomethylated. In a more focused study, tumor suppressor genes were identified that are hypermethylated in the early stages of HCC.…”
Section: Dna Methylation and Hccmentioning
confidence: 99%